2020
DOI: 10.3390/ijms21176382
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Amyloidogenic Activity of Peptides Synthesized on the Basis of the Ribosomal S1 Protein from Thermus Thermophilus

Abstract: Controlling the aggregation of vital bacterial proteins could be one of the new research directions and form the basis for the search and development of antibacterial drugs with targeted action. Such approach may be considered as an alternative one to antibiotics. Amyloidogenic regions can, like antibacterial peptides, interact with the “parent” protein, for example, ribosomal S1 protein (specific only for bacteria), and interfere with its functioning. The aim of the work was to search for peptides based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 32 publications
0
40
0
Order By: Relevance
“…At the same time, using computational and experimental approaches, we described specific amyloidogenic regions within the domains of the S1 protein, which can be potential sites for modulating the aggregation properties of bacterial ribosomal S1 proteins [ 9 , 205 , 206 , 207 ]. Based on the predicted amyloidogenic regions, amyloidogenic peptides were synthesized, some of which exhibited antimicrobial activity in vitro tests [ 16 ].…”
Section: Mechanisms Of Antimicrobial Action Of Peptidesmentioning
confidence: 99%
See 3 more Smart Citations
“…At the same time, using computational and experimental approaches, we described specific amyloidogenic regions within the domains of the S1 protein, which can be potential sites for modulating the aggregation properties of bacterial ribosomal S1 proteins [ 9 , 205 , 206 , 207 ]. Based on the predicted amyloidogenic regions, amyloidogenic peptides were synthesized, some of which exhibited antimicrobial activity in vitro tests [ 16 ].…”
Section: Mechanisms Of Antimicrobial Action Of Peptidesmentioning
confidence: 99%
“…Self-aggregation of a protein or its coaggregation with an effector peptide should lead to blocking of protein functions and a decrease in the viability of the bacterial cell. In our study, we used methods of thioflavin T fluorescence, electron microscopy, spectrophotometry and mass-spectrometry to assess the amyloidogenic and antibacterial activity of peptides synthesized on the basis of the ribosomal S1 protein from Thermus thermophilus [ 16 ]. It has been experimentally demonstrated that amyloidogenic regions of the ribosomal S1 protein can be used as candidates for the development of new antibacterial peptides [ 16 ].…”
Section: Mechanisms Of Antimicrobial Action Of Peptidesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important that the S1 domain is a structural variant of the oligosaccharide/oligonucleotide-binding fold (OB-fold) [ 23 , 24 ] and can exhibit amyloidogenic properties, like another analog of the OB-fold, the cold shock domain [ 25 ]. Previously, peptides with amyloidogenic properties and antimicrobial activity against Thermus thermophilus were synthesized and studied based on the sequences of the S1 domains of the ribosomal S1 protein of the model organism T. thermophilus [ 26 ].…”
Section: Introductionmentioning
confidence: 99%